The impact of the fuzzy front end on new product development success in Japanese NPD projects - Birgit Verworn; Cornelius Herstatt; Akio Nagahira (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
In a study of Japanese New Product Development (NPD) projects, the fuzzy front end of innovation is explored. Our conceptual model is based on the information-processing perspective. A structual equation model was fitted to data from 497 NPD projects from Japanese mechanical and electrical engineering firms to test the proposed model. The empirical analysis found support for all hypotheses except for one. Our study suggests that an early reduction of market and technical uncertainty and a draft initial planning prior to development have a positive impact on NPD project success. The model accounts for 17% of the variance of the efficiency and 24% of the variance of the effectiveness dependent variable. Thus, the front end phase is an important driver of NPD project success. Implications of the model are discussed.
Keywords: 650